People's Century, 20th : From the Dawn of the Century to the Start of the Cold War - Hodgson, Godfrey (London BBC Books, 1995)
The first of two volumes of a work based on a 26-part BBC1 series which tells the story of the 20th century by concentrating on the role played by ordinary people. The book takes the story up to the struggles for independence of colonial peoples.
Include Color Illustration and Index
Keywords: History, Modern -- Twentieth century